Performance Persistence. - Brown, Stephen J; Goetzmann, William N (Journal of Finance, 1995)
The authors explore performance persistence in mutual funds using absolute and relative benchmarks. Their sample, largely free of survivorship bias, indicates that relative risk-adjusted performance of mutual funds persists; however, persistence is mostly due to funds that lag the S&P 500. A profit analysis indicates that poor performance increases the probability of disappearance. A year-by-year decomposition of the persistence effect demonstrates that the relative performance pattern depends upon the time period observed and it is correlated across managers. Consequently, it is due to a common strategy that is not captured by standard stylistic categories or risk adjustment procedures.